2016
DOI: 10.3892/etm.2016.3353
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and the clinical and surgical features of fungal prosthetic joint infections: A retrospective analysis of eight cases

Abstract: Fungal prosthetic joint infections (PJI) and reports of their clinical investigation are rare. In addition, there has been little evidence regarding the outcome of the two-stage exchange protocol for the treatment of fungal PJI. In order to investigate the risk factors and clinical, microbiological and pathological features of fungal PJIs, as well as the effects of the two-stage exchange protocol on their outcome, the present study analyzed eight retrospective fungal PJI cases, involving four cases affecting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 36 publications
0
26
0
1
Order By: Relevance
“…The reason may be that some patients underwent artificial joint replacement surgery in another hospital, and they had already received treatment for PJI with broad-spectrum antibiotics and re-operation in those hospitals. 21 The small number of cases in our study may have affected the statistical analysis. A Spanish multicenter study also reported a significant increase in the incidence of PJI caused by fungi.…”
Section: Discussionmentioning
confidence: 90%
“…The reason may be that some patients underwent artificial joint replacement surgery in another hospital, and they had already received treatment for PJI with broad-spectrum antibiotics and re-operation in those hospitals. 21 The small number of cases in our study may have affected the statistical analysis. A Spanish multicenter study also reported a significant increase in the incidence of PJI caused by fungi.…”
Section: Discussionmentioning
confidence: 90%
“…To our knowledge, this is the first study to establish an association between a patient's surgical history and subsequent development of fungal PJI. In a study done by Geng et al [28], which was a retrospective analysis of eight cases of fungal PJIs, six had undergone additional surgery on the infected joint following primary total joint arthroplasty and preceding diagnosis of fungal PJI. In a second smaller study from Spain, comprising 10 patients with fungal PJIs, nine had previous bacterial infections, received antibiotics for more than 15 days and required multiple surgeries [29].…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter fungal PJI study of 31 patients reported an average ESR and CRP of 54 mm/hr and 17.5 mg/L, respectively. 7 Geng et al 9 reported an average ESR and CRP of 75 mm/hr and 6 mg/dl in 87.5% (7 of 8) of patients. Klatte et al 14 found patients with fungal PJI to have elevated mean CRP levels (22 mg/L; range 6-90.1 mg/L) with normal white blood cell (WBC) counts (mean, 5.7 cell/nL; range 4.6-8.0).…”
Section: Serum Analysismentioning
confidence: 98%
“…Multiple revision surgeries and prolonged hospitalizations also increased the risk of fungal PJI. 7,9 Among all the risk factors and associated comorbidities for fungal PJI, immunosuppression has the highest correlation with fungal infections because of its close association with the innate immune response. 10 Innate immune pattern recognition receptor cells mount a specific fungal response with C-type lectin receptors, pentraxin-3, and Toll-like receptors.…”
Section: History and Physicalmentioning
confidence: 99%